Absorption diffusion refrigeration unit and test bench for its generator - Kozhemiachenko A. V., Petrosov S. P., Maslov O. S., Nikishin V. V. (Education and science in the modern context, 2018)
the article presents the design of absorption-diffusion refrigeration unit distinguishes than that, with the aim of increasing efficiency, a reflux condenser and absorber is fitted with cooling jackets, and the evaporator has a collection of melt water, is connected in parallel to the shirts of the reflux condenser and the absorber. The article also presents the design of the test stand generator the above absorption-diffusion refrigeration unit, characterized in that, with the purpose of testing in a wide range of values of the cooling capacity of the test generators, the stand further comprises electrochlorinator with a regulating valve at the entrance, acting as a refrigerator evaporator, heat exchangers with the coils connected among themselves by means of piping and employees fracking, condenser, absorber with reservoir, liquid and gas heat exchangers of the refrigerator, and the water distribution manifold with regulating valves connected to mirzoalimov spaces of the respective h
Keywords: теплообменник; efficiency; экономичность; теплообменный аппарат; испаритель; абсорбер; дефлегматор; абсорбционный диффузионный холодильный; охлаждающая рубашка; сборник талой воды; стенд для испытания генератора; холодопроизводительность; электроколариметр; водораспределительный коллектор; diffusion absorption refrigeration; reflux condenser; absorber; cooling jacket; an evaporator; a defrost water collector; test generator; refrigeration; electrocolorimetric; heat exchanger; water distribution header; the heat exchanger